2021
DOI: 10.1080/00107530.2021.1935191
|View full text |Cite
|
Sign up to set email alerts
|

Power Dynamics in the Clinical Situation: A Confluence of Perspectives

Abstract: Power issues in psychotherapy are often addressed from the perspective of intersectional and societal power, enacted or embodied in the therapy relationship. Following the thinking of Young-Bruehl, who argued for acknowledging the heterogeneity of oppression, this article posits a heterogeneity of power themes in psychotherapy. Four areas of power are highlighted: Professional power, transferential power, socio-political power, and bureaucratic power. All these kinds of power are explored through the case of "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
3
0
2
Order By: Relevance
“…In Power Dynamics, more obvious and identifiable aspects of power are described, although in this and across all three themes we have described a range of felt experiences of power: dynamics that both hold together (dark matter) and pull apart (dark energy) the known universe of established ways of doing and theorizing analysis. In her study of power dynamics in a clinical situation, Malin Fors (2021) makes the point that power can be viewed from many different perspectives, using different frames of reference, but that much of it is unconscious. She acknowledges the increasing appreciation of unconscious power dynamics in contemporary psychoanalytic writing but notes that the emphasis is on intersectional and societal power issues as they appear in the therapeutic relationship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Power Dynamics, more obvious and identifiable aspects of power are described, although in this and across all three themes we have described a range of felt experiences of power: dynamics that both hold together (dark matter) and pull apart (dark energy) the known universe of established ways of doing and theorizing analysis. In her study of power dynamics in a clinical situation, Malin Fors (2021) makes the point that power can be viewed from many different perspectives, using different frames of reference, but that much of it is unconscious. She acknowledges the increasing appreciation of unconscious power dynamics in contemporary psychoanalytic writing but notes that the emphasis is on intersectional and societal power issues as they appear in the therapeutic relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Fors concluded that it was “fruitful to try to hold different perspectives in mind simultaneously” (Fors, 2021, p. 262). Our experience of looking at what happens when key concepts are critiqued, itself an expression of power, revealed the importance of trying to engage with the many possible perspectives on power, but also the difficulty of doing this.…”
Section: Discussionmentioning
confidence: 99%
“…Budiardjo (2006) defines power as the capacity to exert influence over another person or group so that they act in a way that furthers the wishes and goals of the person or group wielding power. Power dynamics in talks are obvious in a variety of ways, and knowing the underlying dynamics helps viewers better appreciate the nuanced dynamics of interpersonal relationships in the series (Fors, 2021). In the same vein as Russell (2013), power results from people's influence over one another to achieve their goals.…”
Section: Representation and Power In Conversationmentioning
confidence: 99%
“…Vi tar likevel utgangspunkt i Flaatens beskrivelse fordi den er en viktig påminnelse om å ta klientens opplevelse på alvor. Vi ønsker dessuten å kommentere Flaatens innlegg fordi det skriver seg inn i helt sentrale debatter i terapiforsknings feltet (se Fors, 2021;Heinonen & Nissen-Lie, 2020;. Hun peker indirekte på hvor vanskelig det er å skille metoden fra terapeuten.…”
Section: Den Omnipotente Terapeut Og Istdp-debatten: Hva Laerte Vi?unclassified
“…Dette er en påstand som mangler empirisk dekning, men vi vet at makt-asymmetrien i den terapeutiske relasjonen kan gjøre at pasienten går altfor langt i å tilpasse seg terapien (Fors, 2021). Insisterende intervensjoner kan dekke et behov i klienten også, og det kan oppstå en suggestiv dynamikk: Terapeuten bruker suggesjon, og klienten lar seg suggerere.…”
Section: Oppsummering Av Debattenunclassified